2015
DOI: 10.2134/agronj14.0218
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Agronomic Advantages of Pea Leaf Type Mixtures under Organic Management

Abstract: Field pea (Pisum sativum L.) is an important organic crop due to its contribution to soil fertility and other rotational benefits. Leafed (wild‐type) pea cultivars tend to be more weed suppressive, but their poor standing ability limits yield compared with semi‐leafless cultivars. Growing mixtures of leafed and semi‐leafless cultivars may improve weed suppression and yield compared with monocultures of the same cultivars by altering canopy morphology. To test this hypothesis, replicated field experiments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The green pea variety was semi-leafless and the forage pea variety was normal leafed. Semi-leafless peas are currently the preferred type for grain production because they are resistant to lodging, but leafed varieties are still preferred for biomass used for forage or GM (Syrovy et al 2015). The amounts of N 2 fixed, aboveground biomass, and the N contained and released by the residues during decomposition, were all greater in forage pea than in green pea (Lupwayi and Soon 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The green pea variety was semi-leafless and the forage pea variety was normal leafed. Semi-leafless peas are currently the preferred type for grain production because they are resistant to lodging, but leafed varieties are still preferred for biomass used for forage or GM (Syrovy et al 2015). The amounts of N 2 fixed, aboveground biomass, and the N contained and released by the residues during decomposition, were all greater in forage pea than in green pea (Lupwayi and Soon 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with previous findings in lentil (Ball et al 1997), but only partially agree with findings in field pea, another weakly competitive pulse crop (Beckie and Kirkland 2003). In a study under organic conditions, weed biomass decreased as field pea crop density increased over a range of 13 to 149 plants m −2 (Syrovy et al 2014). In another study, however, field pea weed biomass did not decrease significantly when crop seeding rate was increased, even in the presence of uncontrolled weeds (Beckie and Kirkland 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Syrovy et al. (2015), under organic growing conditions, reported that a leaf blend resulted in 156 and 18% more seed yield than the L and SL monocultures, respectively. The differences between studies could be due to the differences in cropping systems or simply a function of the single pair of unrelated crop varieties that Syrovy et al.…”
Section: Discussionmentioning
confidence: 99%